Sialyl Tn-Expressing Bladder Cancer Cells Induce a Tolerogenic Phenotype in Innate and Adaptive Immune Cells - Carrascal, M (2014)
Despite the wide acceptance that glycans are centrally implicated in immunity, exactly how they contribute to the tilt immune response remains poorly defined. In this study, we sought to evaluate the impact of the malignant phenotype-associated glycan, sialyl-Tn (STn) in the function of the key orchestrators of the immune response, the dendritic cells (DCs). In high grade bladder cancer tissue, the STn antigen is significantly overexpressed and correlated with the increased expression of ST6GALNAC1 sialyltransferase. Bladder cancer tissue presenting elevated expression of ST6GALNAC1 showed a correlation with increased expression of CD1a, a marker for bladder immature DCs and showed concomitant low levels of Th1-inducing cytokines IL-12 and TNF-α. In vitro, human DCs co-incubated with STn+ bladder cancer cells, had an immature phenotype (MHC-IIlow, CD80low and CD86low) and were unresponsive to further maturation stimuli. When contacting with STn+ cancer cells, DCs expressed significantly less IL-12 and TNF-α. Consistent with a tolerogenic DC profile, T cells that were primed by DCs pulsed with antigens derived from STn+ cancer cells were not activated and showed a FoxP3high IFN-γlow phenotype. Blockade of STn antigens and of STn+ glycoprotein, CD44 and MUC1, in STn+ cancer cells was able to lower the induction of tolerance and DCs become more mature. Overall, our data suggest that STn-expressing cancer cells impair DC maturation and endow DCs with a tolerogenic function, limiting their capacity to trigger protective anti-tumour T cell responses. STn antigens and, in particular, STn+ glycoproteins are potential targets for circumventing tumour-induced tolerogenic mechanisms.